1999
DOI: 10.1086/302593
|View full text |Cite
|
Sign up to set email alerts
|

A Second Locus for Familial Generalized Epilepsy with Febrile Seizures Plus Maps to Chromosome 2q21-q33

Abstract: We report a clinical and genetic study of a family with a phenotype resembling generalized epilepsy with febrile seizures plus (GEFS+), described by Berkovic and colleagues. Patients express a very variable phenotype combining febrile seizures, generalized seizures often precipitated by fever at age >6 years, and partial seizures, with a variable degree of severity. Linkage analysis has excluded both the beta 1 subunit gene (SCN1B) of a voltage-gated sodium (Na+) channel responsible for GEFS+ and the two loci,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
1
9

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(120 citation statements)
references
References 28 publications
3
107
1
9
Order By: Relevance
“…In 1999, linkage analysis in 2 large families localized a second GEFS+ locus to an interval of chromosome 2q24 that includes a sodium channel gene cluster (12,13). Sequencing of SCN1A demonstrated that affected individuals are heterozygous for missense mutations in highly evolutionarily conserved amino acid residues, T875M in 1 family and R1648H in the other (14).…”
Section: Inherited and De Novo Mutations Of Scn1a In Gefs+ Severe Myomentioning
confidence: 99%
“…In 1999, linkage analysis in 2 large families localized a second GEFS+ locus to an interval of chromosome 2q24 that includes a sodium channel gene cluster (12,13). Sequencing of SCN1A demonstrated that affected individuals are heterozygous for missense mutations in highly evolutionarily conserved amino acid residues, T875M in 1 family and R1648H in the other (14).…”
Section: Inherited and De Novo Mutations Of Scn1a In Gefs+ Severe Myomentioning
confidence: 99%
“…The most common symptoms of GEFSϩ are FS and FS plus, in which the seizures are triggered by hyperthermia and occur after 6 years of age (Scheffer and Berkovic, 1997;Baulac et al, 1999). To investigate whether Scn1a mutant rats are susceptible to thermal stimuli, we used a hot water bath to induce FS (Klauenberg and Sparber, 1984)…”
Section: Susceptibility To Hismentioning
confidence: 99%
“…A second locus, GEFS+2, was mapped in 1999 to a 20-cM interval of chromosome 2q24 that contained the α subunit genes SCN1A, SCN2A, and SCN3A by analysis of two large families (6,50). Screening affected individuals from both families using conformation sensitive gel electrophoresis of amplified exons identified two missense mutations in the SCN1A gene, R1648H and T875M (27).…”
Section: Generalized Epilepsy With Febrile Seizures Plus-mentioning
confidence: 99%